Let's Play: Using Systemic and Experiential Techniques in the Play Therapy Instruction of MFT Masters' Students. Issue 1 (1st January 2019) - Barker, Bryce; Cannell, Conrad; Naylor, Sarah; Pearl, Kaity; Stewart, Evan; Oka, Megan
Abstract: Marriage and family therapists are uniquely poised to work with entire families, including children. It is surprising then, that so few MFTs affiliate with play therapy. Many COAMFTE accredited masters' programs offer some form of play therapy training, but therapists often report feeling uncomfortable with play therapy (Gil, 2015). In this paper, we offer a condensed refresher course on play therapy for MFTs, including suggested readings, materials, and instructions to expand training from a 2-day seminar to a 14-week course. We discuss the strengths and weaknesses of offering play therapy instruction as a semester long required course for masters' students.